Efficacy and safety of fire needle vs conventional acupuncture in the treatment of postherpetic neuralgia: A protocol for systematic review and meta analysis. Issue 41 (9th October 2020) - Lu, Lunbin; Xiong, Jun; Chen, Zhijun; Zhou, Xingchen; Chen, Jun; Tang, Genhua; Zhu, Siyuan; Zhong, Zhiying; Guo, Han
Abstract: Background: Fire needle therapy has the double function of acupuncture and moxibustion, which has both the stimulation of needle and the warm stimulation of moxibustion. As an important part of acupuncture and moxibustion, fire needle has been widely used in clinical treatment since ancient times in China. Postherpetic neuralgia (PHN) is a kind of chronic and solid neuropathic pain with persistent and intense pain after the skin lesion of sores has been completely eliminated. The clinical treatment of PHN is mostly integrated therapy. In recent years, many literatures have reported that the curative effect of fire needle on PHN is accurate. The purpose of this protocol is to describe how to accumulate evidence for further understanding of the status quo and reliability of clinical practice in the treatment of PHN with fire needle. Methods: Seven electronic databases were used to retrieve the literature for the PHN randomized controlled trials, including 3 English databases (PubMed, EMBASE, the Cochrane Central Register of Controlled Trials [Cochrane Library]) and 4 Chinesedatabases (Chinese National Knowledge Infrastructure, Chinese VIP Information, Wanfang Database, and Chinese Biomedical Literature Database). This systematic review will include all randomized controlled clinical trials using fireneedle therapy for PHN. Pain intensity, safety and cost, quality of life, global perceptionare outcomes. The selection of the study will be completed independently by 2 reviewers, extract the data, and evaluate the quality of the study before selecting the title, abstract, and full text. Revman 5.4 software will be used to perform meta-analyses of randomized controlled trials, where risk ratios for dichotomous data and standardized or weighted mean differences for continuous data are the results. Result: Conclusion: This proposed systematic review will provide up-to-date evidence to assess the effect of fire needle for patients with PHN. Registration: INPLASY202080029.